Recent Advances in Information Hiding and Applications - Pan, Jeng-Shyang.; Huang, Hsiang-Cheh.; Jain, Lakhmi C.; Zhao, Yao. (Intelligent Systems Reference Library,, 2013)
This research book presents a sample of recent advances in information hiding techniques and their applications. It includes: Image data hiding scheme based on vector quantization and image graph coloring The copyright protection system for Android platform Reversible data hiding ICA-based image and video watermarking Content-based invariant image watermarking Single bitmap block truncation coding of color images using cat swarm optimization Genetic-based wavelet packet watermarking for copyright protection Lossless text steganography in compression coding Fast and low-distortion capacity acoustic synchronized acoustic-to-acoustic steganography scheme Video watermarking with shot detection